Notch4 mediates vascular remodeling via ERK/JNK/P38 MAPK signaling pathways in hypoxic pulmonary hypertension - Guo, Mingzhou; Zhang, Mengzhe; Cao, Xiaopei; Fang, Xiaoyu; Li, Ke; Qin, Lu; He, Yuanzhou; Zhao, Jianping; Xu, Yongjian; Liu, Xiansheng; Li, Xiaochen (Respiratory research, 2022)
Hypoxic pulmonary hypertension (HPH) is a chronic progressive advanced disorder pathologically characterized by pulmonary vascular remodeling. Notch4 as a cell surface receptor is critical for vascular development. However, little is known about the role and mechanism of Notch4 in the development of hypoxic vascular remodeling. Lung tissue samples were collected to detect the expression of Notch4 from patients with HPH and matched controls. Human pulmonary artery smooth muscle cells (HPASMCs) were cultured in hypoxic and normoxic conditions. Real-time quantitative PCR and western blotting were used to examine the mRNA and protein levels of Notch4. HPASMCs were transfected with small interference RNA (siRNA) against Notch4 or Notch4 overexpression plasmid, respectively. Cell viability, cell proliferation, apoptosis, and migration were assessed using Cell Counting Kit-8, Edu, Annexin-V/PI, and Transwell assay. The interaction between Notch4 and ERK, JNK, P38 MAPK were analyzed by co-immunoprecipitation. Adeno-associated virus 1-mediated siRNA against Notch4 (AAV1-si-Notch4) was injected into the airways of hypoxic rats. Right ventricular systolic pressure (RVSP), right ventricular hypertrophy and pulmonary vascular remodeling were evaluated. In this study, we demonstrate that Notch4 is highly expressed in the media of pulmonary vascular and is upregulated in lung tissues from patients with HPH and HPH rats compared with control groups. In vitro, hypoxia induces the high expression of Delta-4 and Notch4 in HPASMCs. The increased expression of Notch4 promotes HPASMCs proliferation and migration and inhibits cells apoptosis via ERK, JNK, P38 signaling pathways. Furthermore, co-immunoprecipitation result elucidates the interaction between Notch4 and ERK/JNK/P38. In vivo, silencing Notch4 partly abolished the increase in RVSP and pulmonary vascular remodeling caused by hypoxia in HPH rats. These findings reveal an important role of the Notch4-ERK/JNK/P38 MAPK axis in hypoxic pulmonary remodeling and provide a potential therapeutic target for patients with HPH.